Charge-Transfer and Non-Rigid-Band Effects in the Graphite Compound LiC6 - MC GOVERN, IGNATIUS (My University, 1981)
A comparison of angle-resolved photoemission energy distributions for pure graphite and the intercalation compound LiC6 show that considerable charge is transferred from Li to C, as expected; but the valence bands do not shift uniformly upon intercalation, in contradiction to the rigid-band approximation. Backfolded bands imposed by the two-dimensional Li superlattice are directly identified for the first time.
PUBLISHED
Keywords: Physics